(untitled) (Global Journal of Human-Social Science, 2021)
This study examined the effect of organizational safety climate on the job satisfaction levels of workers at the Picorna Hotel, Radach Lodge and Conference Center, and University of Development Studies Guest House in the Tamale Metropolis in Ghana. A cross-sectional survey was used as the research design. A total of 127 respondents were selected using the stratified random sampling technique. Questionnaires that contained the 50-item Occupational Safety Climate Questionnaire and the 11-item Job Satisfaction Scale was used to collect data. Data was analyzed with the Simple Linear Regression test, PROCESS" Macro Script Moderation test, One-Way Analysis of Variance test and the Independent t test. Results indicated that organizational safety environment predicts employees’ job satisfaction. Particularly, the role played by hotel management had the most influence on employees’ job satisfaction. In addition, differences in workers’ "age" and "rank" had no moderation effect on the relationship between organizational safety environment and job satisfaction. Furthermore, no significant difference was found between the organizational safety environment among the selected hotels.